2022
DOI: 10.1002/jee.20483
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of engineering instructors' pedagogical adaptations early in the COVID‐19 pandemic

Abstract: Background: Many instructors made an emergency shift to online teaching during the Spring 2020 semester. There is reason to expect that instructors would have dramatically changed their pedagogy and teaching philosophies.At the same time, there are reasons that engineering instructors might be hesitant to introduce some changes to their courses.Purpose/Hypothesis: This study explores pedagogical and philosophical adaptations using instructors' accounts of emergency remote teaching during the Spring 2020 semest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The sudden shift to remote instruction prompted instructor decision‐making processes and shifts in practice (Koretsky, 2022; Manierre et al, 2022), which simultaneously were influenced by their trajectory of practice and influenced that trajectory as well. The responses could range, for example, from instructors trying to replicate their in‐person instruction as closely as possible in the remote setting to considering the learning objectives and the social toll of the pandemic, identifying the affordances and constraints of online learning, and redesigning course learning activities and assessments to appropriately respond as well as possible.…”
Section: Ecosystems: Exploring Instructional Perturbationsmentioning
confidence: 99%
“…The sudden shift to remote instruction prompted instructor decision‐making processes and shifts in practice (Koretsky, 2022; Manierre et al, 2022), which simultaneously were influenced by their trajectory of practice and influenced that trajectory as well. The responses could range, for example, from instructors trying to replicate their in‐person instruction as closely as possible in the remote setting to considering the learning objectives and the social toll of the pandemic, identifying the affordances and constraints of online learning, and redesigning course learning activities and assessments to appropriately respond as well as possible.…”
Section: Ecosystems: Exploring Instructional Perturbationsmentioning
confidence: 99%
“…We know that COVID-19 disruptions have forced college instructors to make an emergency shift to online teaching, including faculty in engineering. Manierre et al (2022) found that in the beginning of the pandemic, engineering instructors, though reluctant at first, decided to modify their engineering courses and engineering pedagogy (i.e., grading policies, expectations, general and individualized accommodations) to alleviate some of the burdens of pandemic-related stressors from students. First-year engineering students have found a sense of togetherness with their teammates after the switch to online instruction during COVID-19 interruptions.…”
Section: The Impact Of the Covid-19 Interruptions On Persistencementioning
confidence: 99%
“…College completion refers to the process and conditions that enable students to meet all academic requirements necessary to obtain their college degree. This process is evaluated through graduation rates and encompasses the implementation of educational policies and specific supports that help students reach their academic and professional goals on time (Huerta-Manzanilla, Ohland, & Peniche-Vera, 2021).. Permanency refers to strategies and programs designed to ensure that students complete their college studies by addressing academic, social, and personal factors that may affect their continuance (Manierre, Dewaters, Rivera, & Whalen, 2022).. University induction refers to the process of orienting and welcoming new students to the university environment, facilitating their understanding of the academic structures and available support services (Díaz-Noguera, Hervás-Gómez, De la Calle-Cabrera, & López-Meneses, 2022). Integration and adaptation to the new formative context involves pedagogical and psychological support to facilitate students' adaptation to the demands and environment of higher education, ensuring their psychological well-being and effective integration (Yurina, Khapacheva, Khakunova, & Autleva, 2019).…”
Section: Towards a Multifaceted And Versatile Model Of Educationmentioning
confidence: 99%